Within- and Trans-Generational Environmental Adaptation to Climate Change: Perspectives and New Challenges - Bautista Naim M.; Crespel Amélie (FRONTIERS MEDIA SA, 2022)
The current and projected impacts of climate change are shaped by unprecedented rates of change in environmental conditions. These changes likely mismatch the existing coping capacities of organisms within-generations and impose challenges for population resilience across generations. To better understand the impacts of projected scenarios of climate change on organismal fitness and population maintenance, it is crucial to consider and integrate the proximate sources of variability of plastic and adaptive responses to environmental change in future empirical approaches. Here we explore the implications of considering: (a) the variability in different time-scale events of climate change; (b) the variability in plastic responses from embryonic to adult developmental stages; (c) the importance of considering the species life-history traits; and (d) the influence of trans-generational effects for individual survival and population maintenance. Finally, we posit a list of future challenges with questions and approaches that will help to elucidate knowledge gaps, to better inform conservation and management actions in preserving ecosystems and biodiversity.